SUGAR CONTENT AS AFFECTED BY FRUITS SIZE AND SEED NUMBER OF SAPODILLA IN MADURA - Eko Setiawan (Universitas Trunojoyo Madura, 2016)
Sapota fruits are highly perishable due to their climacteric nature. The rapid softening of fruits is primarily due to high activity of many oxidative enzymes and liberation of ethylene. Harvest maturity plays a crucial role in deciding the marketability of climacteric fruits in general. We investigate sugar contents on sapodilla fruits related on fruits size and seed number. The experiment was conducted using 100 sapodilla fruits harvested from farmer in Madura. Fruit size and weight were recorded. Each fruit was separated into fruit and seed, and then weight was recorded with an analytical balance. The number and weight of seeds were counted. Total soluble solid (TSS; °Brix) was measured using arefractometer (PAL-1, Atago, Tokyo Tech). The number of seed and seed weight of sapodilla have correlation with Total Soluble Solid (TSS). The higher amount of seed equal with increasing seed weight, and effect to decrease TSS in sapodilla fruits. In additional, increasing seed weight have correlation with fruit weight, while TSS was decrease slightly. The average diameter and length of sapodilla fruit were 4.01 and 5.53 cm, respectively. Keywords: fruit size, Sapodilla, TSS content, seed number.